The Effect of Debt to Assets Ratio, Return on Assets, and Total Assets Turnover on Financial Distress - Hidayat, Andreas Josafat; Bintara, Rista (Tazkia Islamic University College, 2025)
This study aims to analyze the effect of Debt Assets Ratio, Return on Assets, and Total Assets Turnover on Financial Distress in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. The independent variables in this study are Debt Assets Ratio, Return on Assets, and Total Assets Turnover, while the dependent variable is Financial Distress which is measured using the Altman Z-Score. The data used are secondary data from property and real estate companies listed on the IDX and taken from the official website www.idx.co.id. This study uses a purposive sampling method by selecting 16 companies that meet the criteria as samples so that there are a total of 64 observation data. The analysis method used is multiple linear regression with the help of SPSS 26. The study results indicate that the Debt to Assets Ratio has a negative effect on Financial Distress, Return on Assets and Total Assets Turnover have no impact on Financial Distress.